Serum lipid profile in pregnancy and its correlation with preeclampsia and its impact on severity of preeclampsia - Datti, Sujatha; Reddy, Swathi Aswath; Tejaswi, Naga (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To compare the changes in the lipid profile in pre-eclampsia, eclampsia and normal pregnancy and to know the severity of preeclampsia depending on the lipid derangement. Methods: This is the hospital based observational analytical study with 30 pregnant women in each study and comparison group at Vydehi Institute of Medical Sciences. India. Lipid profile was run in each participant and statistical analysis was performed by STATA 11.2. Results: The mean value of serum total cholesterol, serum triglycerides, low density lipoprotein and very low-density lipoprotein in the study group were significantly raised compared to comparison group. The mean high density lipoprotein levels were lower in study group compared to comparison group which was statistically significant. Total cholesterol, LDL and VLDL was increased in eclampsia group and severe preeclampsia group. No significant difference was found between serum triglyceride levels, HDL and severity of preeclampsia. Conclusions: LDL and VLDL were significantly higher in severe preeclampsia and eclampsia; but no significant difference found between serum triglyceride levels and HDL levels. Keywords: dyslipidemia, lipoprotein, preeclampsia